2021
DOI: 10.2147/ppa.s344878
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Beliefs About Post-Transplant Immunosuppressants Over Time and Its Relation to Medication Adherence and Kidney Graft Dysfunction: A Follow-Up Study

Abstract: Purpose The main aim was to evaluate the changes in beliefs about immunosuppressants over a 3-year period in patients after kidney transplantation. The second aim was to investigate the relationship between beliefs, medication adherence, and selected clinical outcomes such as graft functioning. Patients and Methods This observational follow-up study was conducted in the outpatient post-transplant clinic at the University Hospital Hradec Kralove in the Czech Republic. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Adherence to immunosuppressants (implementation phase) was assessed by the written version of the Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS © ) ( Dobbels et al, 2010 ), translated from English to the Czech language ( Kostalova et al, 2021 ). The BAASIS consists of five self-report items: one on initiation; three on implementation and one on persistence to the prescribed immunosuppression regimen.…”
Section: Methodsmentioning
confidence: 99%
“…Adherence to immunosuppressants (implementation phase) was assessed by the written version of the Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS © ) ( Dobbels et al, 2010 ), translated from English to the Czech language ( Kostalova et al, 2021 ). The BAASIS consists of five self-report items: one on initiation; three on implementation and one on persistence to the prescribed immunosuppression regimen.…”
Section: Methodsmentioning
confidence: 99%
“…The patients included in the study were 39.7% female (n = 60) and 60.3% male (n = 91). The mean age at transplantation was 11.51 ± 4.97 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The mean serum creatinine and GFR levels were 2.14 ± 2.66 (0.38-16.09) and 67.22 ± 30.44 (3-128), respectively.…”
Section: Re Sultsmentioning
confidence: 99%
“…6 In another study with adult kidney transplant recipients, it was suggested that good treatment compliance may be associated with better kidney function. 7 Also, in pediatric renal transplant recipients, it was reported that medication non-adherence and estimated GFR values were related. 8 GFR and creatinine are one of the two basic parameters to be used to evaluate organ functions after kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 After kidney transplant, lifelong immunosuppressive therapy to prevent organ rejection is mandatory. 15,16 It is composed of the daily administration of 2-3 drugs, [17][18][19][20] in addition to treatment for other comorbidities, which implies an average of 10 different medications prescribed per day. [21][22][23] Consequently, the post-kidney transplant patient is susceptible to adverse drug reactions, in addition to a greater risk of infections, diabetes, increased blood pressure, and weight gain.…”
Section: Introductionmentioning
confidence: 99%